Influence of regional iron on the motor impairments of Parkinson's disease: A quantitative susceptibility mapping study. Issue 5 (22nd August 2016) - Guan, Xiaojun; Xuan, Min; Gu, Quanquan; Xu, Xiaojun; Huang, Peiyu; Wang, Nian; Shen, Zhujing; Xu, Jingjing; Luo, Wei; Zhang, Minming
Abstract : Purpose: Because the roles of striatal‐thalamo‐cortical and cerebello‐thalamo‐cortical circuits in the heterogeneous motor impairments of Parkinson's disease (PD) are becoming recognized, this study was designed to investigate the relationships between regional iron in the cardinal subcortical nuclei in these circuits and the different motor impairments. Materials and Methods: Sixty‐two PD patients and 40 normal subjects were included and accepted for Enhanced T 2 ‐Star Weighted Angiography Scanning (3.0T). According to the Unified Parkinson's Disease Rating Scale, patients were divided into tremor‐dominant (PD‐TD) and akinetic/rigid‐dominant groups (PD‐AR). The intergroup differences of magnetic susceptibility in those cardinal nuclei were measured. Correlation analyses between magnetic susceptibility and motor impairments were performed in all patients. Results: Nigral magnetic susceptibility significantly increased for each PD group compared with controls ( P < 0.001 for PD‐TD; P  = 0.001 for PD‐AR). Magnetic susceptibility in the dentate nucleus (DN) and red nucleus (RN) for the PD‐TD patients were significantly increased compared with controls ( P < 0.001 and P  = 0.004, respectively). Magnetic susceptibility in these regions was also significantly correlated with tremor severity ( r  = 0.444, P  = 0.001 for DN; r  = 0.418, P  = 0.001 for RN). Significant correlation between caudate magnetic susceptibility and akinetic/rigid severity were observed ( r  = –0.322, P  = 0.015). Conclusion: This study provides evidence that nigral iron accumulation is a common characteristic in PD, while iron accumulation in the DN and RN is correlated with tremor symptoms. Our data also indicate that caudate iron content may be a potential marker for akinetic/rigid progression. Level of Evidence : 3 J. MAGN. RESON. IMAGING 2017;45:1335–1342